Coronary Artery Fistula and Pectus Excavatum Paradox - Mohammad Hashim Jilani; Hina Khawar Jamali; Fahad Waqar; Mohamed Effat (Case Reports in Cardiology)
Pectus excavatum is the most common congenital chest wall deformity. Its effects on cardiopulmonary function, exercise capacity, and body image are variable across affected patients. Management practices for pectus deformity vary considerably, but most authors agree on the need for surgical correction if pectus index is >3.0 and there is evidence of cardiac compression on imaging. We encountered a case of a middle-aged man with severe pectus deformity and a coincidental large coronary artery to right atrium fistula. Despite a pectus index of 4.8 and severe right heart compression on thoracic imaging, he had not developed any symptoms or hemodynamic complication from this pectus deformity. Additionally, hemodynamic studies revealed normal left and right heart function, normal pulmonary artery pressures, and absence of any evidence of myocardial ischemia or significant left-to-right shunt. These abnormalities would have been expected with a coronary fistula of this size. His pectus deformity and coronary fistula had opposing hemodynamic effects, thus protecting him from severe complications of either. Presently, an association between congenital coronary fistulae and pectus excavatum is not known, and this is one of the very first reported cases of these two congenital abnormalities coexisting in a patient. Additionally, concurrence of these two conditions poses a unique therapeutic challenge due to their opposing hemodynamic effects.